THE INFLUENCE OF SOCIAL MEDIA MARKETING ON PURCHASE DECISION THROUGH BRAND AWARENESS OF LOCAL BRAND SULAWESI UTARA CAP TIKUS 1978 - Gratcia Natasya Bonaldy; Joy Elly Tulung; Emilia M. Gunawan (Universitas Sam Ratulangi, 2023)
This study aims to find out the influence of social media marketing toward purchase decision with brand awareness as the mediate variable of local brand Sulawesi Utara Cap Tikus 1978. The research method used in this research is quantitative methods. Path Analysis method is used to analyze the effect of the independent variable on the dependent variable and mediating variable. The population in this research were the society of Kota Manado with research characteristic of age between 21 to 40 years old who bought Cap Tikus 1978. This study conducts with 120 respondent. The result of this research indicated that Social Media Marketing has positive and significant influence on Brand Awareness, Social Media Marketing has positive and significant influence on Purchase Decision, Brand Awareness has positive and significant influence on Purchase Decision. The results of this study also shown that the Brand Awareness can be used as a mediating variable for the influence of Social Media Marketing on Purchase Decision through Brand Awareness of Local Brand Sulawesi Utara Cap Tikus 1978 with the indirect effect is 0,543. Keywords: social media marketing, purchase decision, brand awareness